Messenger in The Barn: networking in a learning environment - Malcolm Rutter (Association for Learning Technology, 2009)
This case study describes the use of a synchronous communication application (MSN Messenger) in a large academic computing environment. It draws on data from interviews, questionnaires and student marks to examine the link between use of the application and success measured through module marks. The relationship is not simple. Total abstainers and heavy users come out best, while medium level users do less well, indicating the influence of two factors. The discussion section suggests possible factors. The study also highlights the benefits of support and efficiency of communication that the application brings. Although there have been many studies of synchronous communication tool use in the office and in social life, this is one of the first to examine its informal use in an academic environment.